On-Surface Ullmann-Type Coupling Reactions of Aryl Halide Precursors with Multiple Substituted Sites - Qiwei Liu; Yuhong Gao; Chi Zhang (Nanomaterials)
The fabrication of low-dimensional nanostructures through on-surface synthesis has emerged as a promising strategy for developing high-precision electronic devices. Among various reactions, Ullmann-type coupling (with carbon–halogen bond activation) stands out in this field as a prevalent methodology due to its straightforward activation process, highly programmable characteristics, and remarkable synthetic efficiency. To date, on-surface Ullmann-type coupling reactions of aryl halide precursors have been extensively studied with the assistance of in situ characterization techniques. The resulting carbon-based nanostructures exhibit high structural diversity and significant potential for applications in molecular electronics. This review categorizes recent progress in the precise preparation of carbon-based nanostructures based on molecular precursors with distinct halogen substituted sites, including para-, meta-, and ortho-sites, peri- and bay-regions, and their combination. In addition, systematic analysis and comparative discussion of their respective characteristics is also provided.